(untitled) (Colombia Medica, 2009)
The main cause of maternal mortality in Colombia is preeclampsia; even though it is a major public health problem its etiology and physiopathology remain unknown. However it is believed that endothelial dysfunction plays a central role in the development of this disease. Many clinical trials have been carried out to demonstrate the effect of certain interventions to prevent preeclampsia and improve pregnancy outcomes. Our hypothesis is that the reduction of preeclampsia risk could be achieved through an appropriate health system that would provide an opportune and effective prenatal care to pregnant women allowing early diagnosis and treatment of frequent nutritional and health related problems.